Cytokine level in blood serum of patients with osteoarthrosis - Filipenko, Volodymyr; Leontyeva, Frieda; Morozenko, Dmytro; Korzh, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article examines pathogenetic and diagnostic roles of the following cytokines in osteoarthrosis of large joints: interleukin 1 beta (IL-1β), interleukin 1RA (IL-1RA), interleukin 4 (IL-4), interleukin 6 (IL-6) and tumour necrosis factor-alpha (TNF-α). It was revealed that levels of IL-1β and IL-6 increased from osteoarthrosis stages I-II to III-VI. IL-1RA concentration in patients’ blood at stages III-VI was lower versus I-II, IL-4 being higher only at stages III-IV of the disease, while TNF-α remained within normal values. Such changes of interleukin content in blood serum of patients with osteoarthrosis demonstrated severe immunological disturbances in their organism. A correlation between cytokine production levels at different stages of osteoarthrosis is indicative of the development of a natural induction of an acute inflammatory process in joints.